Estimulación temprana y su incidencia en el desarrollo psicomotor fino de los niños del subnivel 1 de educación inicial de la Unidad Educativa Rosa Chavez Cantón Babahoyo - Borja Manzo, Luisa Adubel (2023)
Early stimulation is relatively important since it helps develop motor skills in children, without any difference, it can be done at home or in specialized places for it, so this case study seeks to analyze the incidence of early stimulation in the fine psychomotor development in children of sublevel 1 of the Rosa Chávez Educational Unit of the city of Babahoyo, among the objectives to be overcome we have to establish the methods used by teachers, describe the psychomotor techniques and recognize what didactic resources they have. The study population is made up of 163 people, including the director, teachers and parents, but only 89 people are considered for the study. It was concluded that 39% of parents surveyed were unaware of the benefits of early stimulation in their children, both in terms of fine and gross motor skills.